EXEC SUMMARY (Tufts Archival Research Center, 2007)
Handwritten; Confidential; Handwritten announcement reporting that the Wisconsin Action Coalition joined with the Labor Management Committee (LMC), the state AFL-CIO, AFSCME and the Wisconsin Education Action Coalition to put out a fair tax radio campaign in the closing days of the legislatures budget debates.